2019
DOI: 10.18203/2349-2902.isj20194035
|View full text |Cite
|
Sign up to set email alerts
|

Modified Limberg flap versus modified Karydakis flap in pilonidal sinus disease: single surgeon experience

Abstract: Background: The aim of this study was to analyze and compare the results of the modified Limberg flap (MLF) and modified Karydakis flap (MKF) techniques which were performed for the treatment of pilonidal sinus disease (PSD).Methods: The patients who were operated for PSD by the same surgeon between November 2010 and July 2013 in Konya Seydisehir Hospital were retrospectively analyzed. A total of 106 patients were evaluated in this study regarding age, gender, operation time, length of hospital stay, and posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Ahmad et al 2 published that the MKFG had better pain score than the MLFG. Turan 17 published that drain removal time was earlier in the MKFG but it was not significantly different between their two study groups. Ekici et al 12 published that, in their study, the mean time to return to labor was 10 (11.4 ± 4.0) days.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Ahmad et al 2 published that the MKFG had better pain score than the MLFG. Turan 17 published that drain removal time was earlier in the MKFG but it was not significantly different between their two study groups. Ekici et al 12 published that, in their study, the mean time to return to labor was 10 (11.4 ± 4.0) days.…”
Section: Discussionmentioning
confidence: 88%
“…Also, Turan 17 published that the complication rates were similar in both the MLF and MKF techniques. Ekici et al 12 found that there were no significant statistical differences regarding seroma formation, wound site infection, and wound dehiscence.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations